The Transformation of Employment Regulation in Greece: Towards a Dysfunctional Liberal Market Economy? - Kornelakis, Andreas; Voskeritsian, Horen (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2014)
SummarySince the eruption of the European sovereign debt crisis, the bailout conditions imposed on Greece have gradually shifted their emphasis from ‘‘tidying up” public finances towards ‘‘improving the competitiveness” of the economy. In the process, collective bargaining has been targeted as one of the priority areas for reform, which resulted in a gradual dismantling of the system. The main aim of this article is to analyse the changes in the institutional framework of employment regulation, using insights from the varieties of capitalism literature. It is argued that the on-going injection of liberal market elements into the Greek employment system is likely to transform Greece into a dysfunctional Liberal Market Economy.The changes in the collective regulation of employment ignore the specificities and idiosyncrasies of the Mediterranean model of capitalism and, thus, are likely to leave the country with the ‘‘worst of both worlds”: suboptimal economic performance and diluted social cohesion. The article is structured as follows. First, the debate on varieties of capitalism is considered in light of the Global Crisis. Second, the basic features of the Greek employment relations’ model are discussed. Third, the transformation of employment regulation after the bailout is examined. Fourth, the evolution towards a dysfunctional Liberal Market Economy is analysed. The final section concludes.